Application Of Islamic Financial System In Money Market - Harahap, Muhammad Ihsan; Sakina, Sakina (Universitas Dehasen Bengkulu, 2024)
The money market is a meeting place between parties who have a surplusfunds with parties experiencing a fund deficit, where the funds are short-term,namely funds with maturities of less than one year. Money market in Islamic perspectiveonly allowed on money markets that do not use an interest system and canreplaced with alternative contracts such as mudharabah, musyarakah, al-qard, wadiah, and alsharf and eliminates the elements of gharar and maysir contained therein. ApplicationIslamic financial system in the money market, including Bank Indonesia CertificateSharia (SBIS), SBIS Repurchase Agreement (Repo), State Sharia Securities(SBSN), SBSN Repurchase Agreement (Repo), and Sharia Interbank Money Market (PUAS).